Design of energy management system for microgrid using hybrid energy storage system - Lau, Boon Peng (Nanyang Technological University, 2022)
In an effort to reduce greenhouse gas emissions and to overcome global warming, more renewable sources such as solar Photovoltaic arrays and wind turbine are introduced to our power system. Also, as energy demand is growing rapidly, new methods are required by our power system to achieve high reliability, stability and efficiency. This report highlights the author’s enjoyable experience to collaborate with ERI@N for his Final Year Project dating from Aug 2021 to May 2022 in Nanyang Technological University, School of Electrical and Electronics Engineering. Hybrid Energy storage system for DC islanded microgrid is presented below, which consists of study on hybrid energy storage, power electronic converters, selection of appropriate power converters to control energy flow with high efficiency. A small, scaled down model of solar photovoltaic arrays, batteries, supercapacitors, power converters and loads had been set up. Lastly, the system performance in MATLAB Simulink environment will be evaluated. Solar array is chosen as the main power source with Maximum Power Point Tracker paired with Perturb and Observe algorithm as the control. MATLAB Simulink provides models of battery (Lithium-Ion) and supercapacitor (Electric Double Layer Capacitor) which will be used for this project. A constant DC load with 500W requirement is used to simulate the load for consumers. However, model can be scaled up accordingly to meet different requirements.